2018
DOI: 10.1080/01480545.2018.1491987
|View full text |Cite
|
Sign up to set email alerts
|

Health hazards of nanoparticles: understanding the toxicity mechanism of nanosized ZnO in cosmetic products

Abstract: In recent years, nanoparticles are being used extensively in personal healthcare products such as cosmetics, sunscreens, soaps, and shampoos. Particularly, metal oxide nanoparticles are gaining competence as key industrial constituents, progressing toward a remarkable rise in their applications. Zinc oxide and titanium oxide nanoparticles are the most commonly employed metal oxide nanoparticles in sunscreens, ointments, foot care, and over the counter topical products. Dermal exposure to these metal oxides pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 80 publications
0
41
0
Order By: Relevance
“…In recent years, research on the biological safety of nanoparticles has become a hot topic. The cytotoxicity of many nanoparticles related to food, cosmetics and medicine, such as Ag, TiO 2 and ZnO [24][25][26], has been studied. Studies have shown that Ag NPs can induce cytotoxicity and genotoxicity in human cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on the biological safety of nanoparticles has become a hot topic. The cytotoxicity of many nanoparticles related to food, cosmetics and medicine, such as Ag, TiO 2 and ZnO [24][25][26], has been studied. Studies have shown that Ag NPs can induce cytotoxicity and genotoxicity in human cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the cosmetics industry, ZnONPs are present in daily supplies, such as shampoos, conditioners, soaps, deodorants, sunscreens, and skin care products, and makeup, in general, to function as antibacterial agents, UV-filters, and pigments and for deeper skin penetration, anti-wrinkling, or moisturizing [128][129][130]. For example, sunscreens containing ZnONPs and TiO 2 NPs are effective barriers against ultraviolet light (UV-light) damage to skin and do not leave white or other residues on the skin [131,132].…”
Section: Zno Nanoparticles-induced Toxicity and The Possible Role Of mentioning
confidence: 99%
“…Zinc oxide nanoparticles (ZnO NPs) have been widely used for medicinal purposes, such as photodynamic therapy [1] and piezoelectric nanomaterials for biomedical applications [2,3,4], various consumer products such as cosmetics and food additives, and industrial materials such as plastics, paints, and ceramics [5,6]. However, concerns of their potential toxicity in terms of environmental safety and human health problems have increased alongside the use of these nanoparticles [5,6,7]. Although ZnO NPs have some positive medical applications due to their antibacterial and anticancer effects, brain injury may occur at any time in both human and non-human biological systems because these nanoparticles can break down the blood–brain barrier (BBB) or be uptaken via olfactory sensory neurons in the nose following prolonged exposure or overdose [8,9,10].…”
Section: Introductionmentioning
confidence: 99%